PENGENALAN KOSAKATA BAHASA INGGRIS UNTUK ANAK-ANAK USIA DINI DENGAN GERAK DAN LAGU DI PANTI ASUHAN RUMAH SHALOM SEMARANG - Adiprana Yogatama; Stefani Dewi Rosaria; Devy Angga Gunantar (Bajang Institute, 2022)
On this occasion USM community service team had the opportunity to carry out community service activities at Rumah Shalom Orphanage Semarang. We found most children there difficult to memorize new vocabularies in English. To help our partners solve the problems, the team applies Total Physical Responses (TPR) method with a face to face lecture and discussion (question and answer) approach as well as training or practice methods. Students are asked to follow and answer the vocabulary that has been taught using the music video. After the activity conducted, it can be concluded that the objectives of the service activities at Rumah Shalom Orphanage can be achieved. The material we deliver is very encouraging, informative and new understanding to students about new vocabulary in English. The participants are also able to understand and memorize new vocabulary in English easily.